Exploring the Potential of EEG Signals in Mental State Analysis - Das, Susmita; Paul, Trisha; Bhattacharyya, Chaitali (Medical Research and Its Applications Vol. 3, 2024)
Electroencephalogram (EEG) is a method known as electrophysiology for monitoring and recording the electrical signal activity of the brain. Electroencephalogram (EEG) signals from the human brain have a ground-breaking impact in the field of healthcare industry. EEG is one of the most actively used biosignals as a measurement tool in the Brain-Computer Interface (BCI) to implement “thoughts or intentions” based on human and machine interaction. In the medical field, EEG-based interaction is also used for computer-aided diagnosis for patients and also to help in detecting emotions and body movements. In this paper, the beneficial aspect of EEG is demonstrated which can be a great help for paralysed patients. In this study, especially the consciousness of human beings through analysis of the values of EEG to predict the physical condition of that particular human is observed. The study of characteristics of the signals while the person is moving and when the person intends to move to be diagnosed through BCI can be controlled for humanoid movement through EEG.